Greater Arterial Stiffness in Children with or without Second-generation Antipsychotic Treatment for Mental Health Disorders: Rigidité Artérielle Plus Importante Chez Les Enfants Avec ou Sans Traitement Par Antipsychotiques de la Deuxième Génération Pour des Troubles de Santé Mentale. (July 2021) - Henderson, Amanda M.; Islam, Nazrul; Sandor, George G. S.; Panagiotopoulos, Constadina; Devlin, Angela M.
Objective: Second-generation antipsychotics (SGAs) are used for a variety of mental disorders and are associated with cardiometabolic side effects in children. The objective of this study was to assess the cardiovascular health of children with mental disorders that are SGA-treated or SGA-naive. Methods: SGA-treated ( n = 47) or SGA-naive ( n = 37) children (aged 6 to 18 years) with mental disorders and control children ( n = 83, no mental disorder) underwent assessment for cardiac function and morphology by echocardiography, aortic pulse wave velocity (PWV), and carotid intima-media thickness (cIMT). Body mass index (BMI) z -scores, waist circumference z -scores, systolic and diastolic blood pressure (BP) percentiles for height and sex, and fasting plasma glucose, insulin, triglycerides, and cholesterol were also assessed. Differences between SGA-treated, SGA-naive, and control children were assessed by linear and log-linear regression models. Results: SGA-treated children had greater BMI z -scores and overweight/obesity (BMI ≥ 85th percentile for age and sex) and hypertension than SGA-naive and control children. The PWV geometric mean was 11.1% higher in SGA-treated (95%CI, 3.95 to 18.77) and 12.9% higher in SGA-naive children (95% CI, 5.60 to 20.59) compared to controls in models adjusted for age, sex, BMI, and systolic BP percentile. Left ventricular (LV) end-diastolic dimension/body surface area (BSA), LV end-systolic dimension/BSA, and LV ejection fraction were lower in SGA-treated and SGA-naive children compared to controls in models adjusted for sex and age. Conclusions: Children with mental disorders have greater arterial stiffness and altered cardiac structure/function than children with no mental health diagnosis. SGA treatment in children is not associated with alterations in cardiovascular structure/function.